Genome and Evolutionary Analysis of Nosema ceranae: A Microsporidian Parasite of Honey Bees - Huang, Qiang; Wu, Zhi Hao; Li, Wen Feng; Guo, Rui; Xu, Jin Shan; Dang, Xiao Qun; Ma, Zheng Gang; Chen, Yan Ping; Evans, Jay D. (Frontiers in Microbiology, 2021)
Microsporidia comprise a phylum of single cell, intracellular parasites and represent the earliest diverging branch in the fungal kingdom. The microsporidian parasite Nosema ceranae primarily infects honey bee gut epithelial cells, leading to impaired memory, suppressed host immune responses and colony collapse under certain circumstances. As the genome of N. ceranae is challenging to assembly due to very high genetic diversity and repetitive region, the genome was re-sequenced using long reads. We present a robust 8.8Mbp genome assembly of 2280 protein coding genes, including a high number of genes involved in transporting nutrients and energy, as well as drug resistance when compared with sister species Nosema apis. We also describe the loss of the critical protein Dicer in approximately half of the microsporidian species, giving new insights into the availability of RNA interference pathway in this group. Our results provided new insights into the pathogenesis of N. ceranae and a blueprint for treatment strategies that target this parasite without harming honey bees. The unique infectious apparatus polar filament and transportation pathway members can help to identify treatments to control this parasite.